2001
DOI: 10.1212/wnl.57.4.632
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cortical “disconnection” as a mechanism of age-related cognitive decline

Abstract: These findings provide direct evidence that white matter tract disruption occurs in normal aging and would be consistent with the cortical disconnection hypothesis of age-related cognitive decline. Maximal changes in anterior white matter provide a plausible structural basis for selective loss of executive functions. In addition to providing new information about the biological basis of cognitive abilities, diffusion tensor MRI may be a sensitive tool for assessing interventions aimed at preventing cognitive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

57
513
5
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 730 publications
(577 citation statements)
references
References 28 publications
57
513
5
2
Order By: Relevance
“…Note: To render FA-SES regression plots more interpretable, participants' SES values on the ISP were converted such that higher scores now reflected higher levels of SES (by subtracting each participant's score from 100) (2013) 35:2045-20562004; O'Sullivan et al 2001;Pfefferbaum et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note: To render FA-SES regression plots more interpretable, participants' SES values on the ISP were converted such that higher scores now reflected higher levels of SES (by subtracting each participant's score from 100) (2013) 35:2045-20562004; O'Sullivan et al 2001;Pfefferbaum et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The unique correlations in the senior group raise the possibility that high SES may neuroprotect some agerelated frontal WM integrity declines. The anatomical specificity of the observed SES-frontal relationship may in part reflect that frontal WM tracts, because they are especially vulnerable to age-related declines (Head et al 2004;O'Sullivan et al 2001;Salat et al 2005a, b), also carry greater chance of incurring protective benefits from high SES than other regions.…”
Section: Discussionmentioning
confidence: 99%
“…Executive function has been shown to correlate with age-related declines in diffusion anisotropy and increases in mean diffusivity (O'Sullivan, et al 2001a), and reading ability was correlated with a measure of fiber tract organization in a group of healthy and reading-impaired adults (Klingberg, et al 2000). Reduced integrity of the association white matter fiber tracts was seen in patients with Alzheimer's Disease (Rose, et al 2000) relative to normal controls.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies investigating effects of aging (O'Sullivan, et al 2001a;Rose, et al 2000), depression (Steffens, et al 2002), multiple sclerosis (Edwards, et al 2001;Rovaris, et al 2002), or neurological abnormalities (Mulhern, et al 2001;O'Sullivan, et al 2001b) have demonstrated a connection between white matter properties and cognition. Executive function has been shown to correlate with age-related declines in diffusion anisotropy and increases in mean diffusivity (O'Sullivan, et al 2001a), and reading ability was correlated with a measure of fiber tract organization in a group of healthy and reading-impaired adults (Klingberg, et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A related possibility is that the diffuse bilateral frontal patterns of activation we observed in older subjects across tasks may reflect a nonspecific recruitment that results from failure of inhibitory processes (Logan et al 2002). Recent studies examining white matter diffusion show age-related decreases in white matter integrity that may be related to reduced functional connectivity (O'Sullivan et al 2001;Pfefferbaum et al 2005). Degradation of white matter is particularly prominent in frontal regions.…”
mentioning
confidence: 99%